"Digital Blackwater": The National Security Administration, Telecommunications Companies and State-Corporate Crime. (1st October 2014) - Laura Finley; Luigi Esposito
Abstract : This article examines the National Security Administration's (NSA) coupling with major telecommunications companies for mass surveillance of Americans' communications as a form of state-facilitated state-corporate crime. It addresses the ways that the US surveillance programmes are violating the right to privacy and are excessively secretive, in violation of international human rights laws. Furthermore, given that attacking and defaming whistleblowers is a hallmark of state-corporate crime, this article also examines the treatment of Edward Snowden, the contractor who leaked information about the NSA's programmes to news media. The article also addresses how this widespread and suspicionless spying is antithetical to democracy, undermining the rule of law and dissuading critical dialogue about public policy and national security. We conclude with an examination of why so many Americans are apathetic about these privacy violations, focusing on the consumerist ideology that promotes widespread acceptance of efforts that allegedly result in greater national security.